2016
DOI: 10.1155/2016/2067087
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism in PCOS: Impact on Presentation, Insulin Resistance, and Cardiovascular Risk

Abstract: Aim of Study. To assess status of thyroid function and thyroid disorders particularly subclinical hypothyroidism (SCH) in subjects with polycystic ovarian syndrome (PCOS) and impact of SCH on various clinical and biochemical parameters and cardiovascular risk in PCOS. Methods. Hundred females diagnosed with PCOS as per Rotterdam criteria and 100 normal controls were recruited and were subjected to elaborate anthropometric, clinical, and biochemical assessment. Results. Notable findings included significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 31 publications
8
42
3
3
Order By: Relevance
“…The TG levels were significantly higher in SCH-PCOS patients than in euthyroid PCOS patients; previously higher levels of TG were reported in PCOS patients as a whole group [44]. In non-PCOS patients with SCH, TG levels were also found to be higher or not different from those found in healthy controls [10,44,46]. Thyroid hormones may also modulate the carbohydrate metabolism and a possible association between TSH and fasting glucose levels was previously reported [10].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The TG levels were significantly higher in SCH-PCOS patients than in euthyroid PCOS patients; previously higher levels of TG were reported in PCOS patients as a whole group [44]. In non-PCOS patients with SCH, TG levels were also found to be higher or not different from those found in healthy controls [10,44,46]. Thyroid hormones may also modulate the carbohydrate metabolism and a possible association between TSH and fasting glucose levels was previously reported [10].…”
Section: Discussionmentioning
confidence: 80%
“…In non-PCOS patients with SCH, TG levels were also found to be higher or not different from those found in healthy controls [10,44,46]. Thyroid hormones may also modulate the carbohydrate metabolism and a possible association between TSH and fasting glucose levels was previously reported [10]. It was also reported that metformin usage results in slight reduction of TSH levels [47].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations